¡I did not sign anything!: the non-signatories of the arbitral convention. The structure of article 14 of the peruvian arbitration law - Córdova Schaefer, Jesús (2017)
Modern commercial relations have been making their dynamics more complex over the years and have made of arbitration the best way of conflicts resolution. One of the most complex changes has been the addition of elements in national and international arbitration agreements. It is also of fundamental importance to define who are the parties involved in the arbitration, both parties involved and non-signatories.In this article, the author analyzes the figure of third parties who have not subscribed to the arbitration agreement in light of the Peruvian Arbitration Law.In addition, the author proposes solutions for its better regulation.